Somatostatin 2 Receptors in the Spinal Cord Tonically Restrain Thermogenic, Cardiac and Other Sympathetic Outflows - Bowman, Belinda R.; Bokiniec, Phillip; McMullan, Simon; Goodchild, Ann K.; Burke, Peter G.R. (Frontiers in Neuroscience, 2019)
The anatomical and functional characterization of somatostatin (SST) and somatostatin receptors (SSTR) within the spinal cord have been focused in the dorsal horn, specifically in relation to sensory afferent processing. However, SST is also present within the intermediolateral cell column (IML), which contains sympathetic preganglionic neurons (SPN). We investigated the distribution of SSTR2 within the thoracic spinal cord and show that SSTR2A and SSTR2B are expressed in the dorsal horn and on SPN and non-SPN in or near the IML. The effects of activating spinal SSTR and SSTR2 were sympathoinhibition, hypotension, bradycardia, as well as decreases in interscapular brown adipose tissue temperature and expired CO2, in keeping with the well described inhibitory effects of activating SSTR receptors. These data indicate that spinal SST can decrease sympathetic, cardiovascular and metabolic functions. Unexpectedly blockade of SSTR2 revealed that SST tonically mantains sympathetic, cardiovascular and metabolic functions as activity in all outflows increased. In addition, high doses of two antagonists evoked biphasic responses in sympathetic and cardiovascular outflows where the initial excitatory effects were followed by profound but transient falls in sympathetic nerve activity, heart rate and blood pressure. These latter effects, together with our findings that SSTR2A are expressed on GABAergic, presumed interneurons, are consistent with the idea that SST2R tonically influence a diffuse spinal GABAergic network that regulates the sympathetic cardiovascular outflow. As described here and elsewhere the source of tonically released spinal SST may be of intra- and/or supra-spinal origin.